Assessment of Progressive Collapsing Foot Deformity Using Semiautomated 3D Measurements Derived From Weightbearing CT Scans. (March 2022) - Krähenbühl, Nicola; Kvarda, Peter; Susdorf, Roman; Burssens, Arne; Ruiz, Roxa; Barg, Alexej; Hintermann, Beat
Background: In progressive collapsing foot deformity (PCFD), hind- and midfoot deformities can be hard to characterize based on weightbearing plain radiography. Semiautomated 3-dimensional (3D) measurements derived from weightbearing computed tomography (WBCT) scans may provide a more accurate deformity assessment. In the present study, automated 3D measurements based on WBCT were used to compare hindfoot alignment of healthy individuals to patients with PCFD. Methods: The WBCT scans of 20 patients treated at our institution with either a flexible (N = 10) or rigid (N = 10) PCFD were compared with the WBCT scans of a control group of 30 healthy individuals. Using semiautomated image analysis software, from each set of 3D voxel images, we measured the talar tilt (TT), hindfoot moment arm (HMA), talocalcaneal angle (TCA; axial/lateral), talonavicular coverage (TNC), and talocalcaneal overlap (TCO). The presence of medial facet subluxation as well as sinus tarsi/subfibular impingement was additionally assessed. Results: With the exception of the TCA (axial/lateral), the analyzed measurements differed between healthy individuals and patients with PCFD. The TCA axial correlated with the TNC in patients with PCFD. An increased TCO combined with sinus tarsi impingement raised the probability of predicting a deformity as rigid. Conclusion: Using 3D measurements, in this relatively small cohort of patients, we identified relevant variables associated with a clinical presentation of flexible or rigid PCFD. An increased TCO combined with sinus tarsi impingement raised the probability of predicting a deformity as rigid. Such WBCT-based markers possibly can help the surgeon in decision-making regarding the appropriate surgical strategy (eg, osteotomies vs realignment arthrodesis). However, prospective studies are necessary to confirm the utility of the proposed parameters in the treatment of PCFD. Level of Evidence: Level III, case-control study.